Surgical Correction of Upper Eyelid Ectropion Presenting Dry Eye Symptoms. (1st June 2020) - Cho, In Chang; Kim, Beom-Jun; You, Hi-Jin; Tark, Woo Hyun
Abstract: Background: Upper eyelid ectropion occurs as a post-blepharoplasty complication or involution change, and it causes dry eye symptoms that cannot be resolved with conservative management. Objectives: The aim of this study is to describe the authors' surgical technique of anatomical correction of upper eyelid ectropion, including tarsal scoring incision. Methods: The technique involves the following 4 steps: (1) adhesiolysis at the preaponeurotic layer; (2) undermining and redraping of the pretarsal flap in a pretarsal plane; (3) optional, partial thickness tarsal scoring incision over the central two-thirds; and (4) downward repositioning of the pretarsal flap and lower fixation to the tarsus. Outcomes were assessed based on the position of eyelid margin and the improvement of the dry eye symptoms. Results: A retrospective review of 54 cases of patients who underwent ectropion correction, including tarsal scoring incision, was performed. The eyelid margin was well positioned in 51 patients (94.4%). Of the 32 patients involved in the study assessed with the 7-point Patient Global Impression of Improvement, 29 (90.6%) reported the resolution of dry eye symptoms. Furthermore, in the 22 patients assessed with the Ocular Surface Disease Index, the mean score significantly decreased from 43.2 ± 24.1 before surgery to 29.8 ± 23.3 ( P = 0.006) after surgery. Conclusions: The combination of partial-thickness tarsal plate scoring and lower flap redraping surgical techniques resolved the upper eyelid ectropion, reducing the dry eye symptoms. Level of Evidence: 4: